Value of autopsy in renal malformations: comparison of clinical diagnosis and post-mortem examination - Giordano, G.; Fellegara, G.; Brigati, et al., F. (Acta Biomedica Atenei Parmensis, 2012)
Background and aim: This 6-year retrospective study reports 14 cases of renal malformations, observed in foetuses and newborns. The objective was to evaluate the usefulness of post-mortem examination in cases of renal malformations by a comparison of the post-mortem findings with clinical diagnosis. Methods: This study included laboratory tests, ultrasonography, karyotype and detailed pathological evaluation of the foetuses and newborns by external, macroscopic, microscopic and placental examination. Results: The results of post-mortem examination were of paramount importance: they disclosed renal malformations escaped on prenatal studies (42,86%), provided extensive additional informations (50%), or confirmed the diagnosis hypothesis (7,14%). Conclusions: Thus, this study confirmed the need of pathological examination for foetuses and newborns, after medical abortion and neonatal death. The pathologist’s contribution to the multidisciplinary management of prenatal or postnatal abnormalities is important in particular for further genetic counseling.